Developing high strength and ductility in biomedical Co–Cr cast alloys by simultaneous doping with nitrogen and carbon. (February 2016) - Yamanaka, Kenta; Mori, Manami; Chiba, Akihiko
Graphical abstract: Abstract: There is a strong demand for biomedical Co−Cr-based cast alloys with enhanced mechanical properties for use in dental applications. We present a design strategy for development of Co−Cr-based cast alloys with very high strength, comparable to that of wrought Co−Cr alloys, without loss of ductility. The strategy consists of simultaneous doping of nitrogen and carbon, accompanied by increasing of the Cr content to increase the nitrogen solubility. The strategy was verified by preparing Co−33Cr−9W−0.35N−(0.01–0.31)C (mass%) alloys. We determined the carbon concentration dependence of the microstructures and their mechanical properties. Metal ion release of the alloys in an aqueous solution of 0.6% sodium chloride (NaCl) and 1% lactic acid was also evaluated to ensure their corrosion resistance. As a result of the nitrogen doping, the formation of a brittle σ-phase, a chromium-rich intermetallic compound, was significantly suppressed. Adding carbon to the alloys resulted in finer-grained microstructures and carbide precipitation; accordingly, the strength increased with increasing carbon concentration. The tensile ductility, on the other hand, increased with increasing carbon concentration only up to a point, reaching a maximum at a carbon concentration of ∼0.1 mass% and decreasing with further carbon doping. However, the alloy with 0.31 mass% of carbon exhibited 14% elongation and also possessed very high strength (725 MPa in 0.2% proof stress). The addition of carbon did not significantly degrade the corrosion resistance. The results show that our strategy realizes a novel high-strength Co−Cr-based cast alloy that can be produced for advanced dental applications using a conventional casting procedure. Statement of significance: The present study suggested a novel alloy design concept for realizing high-strength Co−Cr-based cast alloys. The proposed strategy is beneficial from the practical point of view because it uses conventional casting approach—a simpler, more cost-effective, industrially friendly manufacturing process than other manufacturing processes such as thermomechanical processing or powder metallurgy. The developed alloys showed the excellent strength–ductility balance and significantly high strength comparable to that of wrought Co–Cr–Mo alloys, while maintaining acceptable ductility and good corrosion resistance. We described the relationship between microstructures and mechanical and corrosion prosperities of the developed alloys; this provides the fundamental aspect of the proposed strategy and will be helpful for further investigations or industrial realization of the proposed strategy.